# How to Evaluate $\lim_{x\to0}\frac{(1-x)^{1/3}-1}{4^x-3^x}$? [closed]

How to find this limit without using L'Hospital rule

$$\lim_{x\to0}\frac{(1-x)^{1/3}-1}{4^x-3^x}$$

## closed as off-topic by user147263, user91500, SchrodingersCat, Claude Leibovici, user223391 Nov 29 '15 at 5:21

This question appears to be off-topic. The users who voted to close gave this specific reason:

• "This question is missing context or other details: Please improve the question by providing additional context, which ideally includes your thoughts on the problem and any attempts you have made to solve it. This information helps others identify where you have difficulties and helps them write answers appropriate to your experience level." – Community, user91500, SchrodingersCat, Claude Leibovici, Community
If this question can be reworded to fit the rules in the help center, please edit the question.

• What have you tried? Where exactly do you need help? Any ideas at all? Please use the math notation environment that is provided. It is difficult to see, what limit you actually want to calculate. – Alexander Nov 26 '15 at 19:37
• Do you mean: $\lim_{x\to 0}\frac{\frac{1-x}{3}-1}{4^x-3^x}$? – Jan Nov 26 '15 at 19:37
• $\lim_{x\to 0}\frac{(1-x)^\frac{1}{3}-1}{4^x-3^x}$, I think. – mzp Nov 26 '15 at 19:41
• the solution is given by $$\left( -6\,\ln \left( 2 \right) +3\,\ln \left( 3 \right) \right) ^ {-1}$$ – Dr. Sonnhard Graubner Nov 26 '15 at 19:48

Hint: $$\lim_{x\to0}\frac{(1-x)^{1/3}-1}{4^x-3^x}= \lim_{x\to0} \frac {\dfrac{(1-x)^{1/3}-1}{x}} {\dfrac{4^x-1}{x}-\dfrac{3^x-1}{x}}$$ Compute each of the three parts and you're done.

Use, binomial expansion of $(1-x)^{1/3}$ & Taylor's series expansion of $4^x$ & $3^x$ as follows $$\lim_{x\to 0}\frac{(1-x)^{1/3}-1}{4^x-3^x}$$ $$=\lim_{x\to 0}\frac{\left(1+\frac{\frac{1}{3}}{1!}(-x)+\frac{\frac{1}{3}\left(\frac{1}{3}-1\right)}{2!}(-x)^2+\ldots\right)-1}{\left(1+x\ln 4+\frac{x^2}{2!}(\ln 4)^2+\ldots\right)-\left(1+x\ln 3+\frac{x^2}{2!}(\ln 3)^2+\ldots\right)}$$ $$=\lim_{x\to 0}\frac{\frac{\frac{1}{3}}{1!}(-x)+\frac{\frac{1}{3}\left(\frac{1}{3}-1\right)}{2!}(-x)^2+\ldots}{\left(x\ln 4+\frac{x^2}{2!}(\ln 4)^2+\ldots\right)-\left(x\ln 3+\frac{x^2}{2!}(\ln 3)^2+\ldots\right)}$$ Dividing numerator & denominator by $x$, $$=\lim_{x\to 0}\frac{-\frac{1}{3}+\frac{\frac{1}{3}\left(\frac{1}{3}-1\right)}{2!}(x)+\ldots}{\left(\ln 4+\frac{x}{2!}(\ln 4)^2+\ldots\right)-\left(\ln 3+\frac{x}{2!}(\ln 3)^2+\ldots\right)}$$

$$=\frac{-\frac{1}{3}+0}{\left(\ln 4+0\right)-\left(\ln 3+0\right)}$$ $$=\color{red}{-\frac{1}{3\ln\left(\frac{4}{3}\right)}}$$

$Step\,1.$ $(1+x)^a = 1+ax + O(x^2)$ for all a and all $x$ with $|x|<1$

$Step\,2.$ $4^x - 3^x= 4^x\left(1-\left(\frac34\right)^x\right)$

$Step\,3.$ $(3/4)^x = \exp(x \ln(3/4)) = 1+ x \ln(3/4)+ \frac{x^2}2 \ln^2(3/4)+ O(x^3)$.

$Step\,4.$ The limit $L= \lim_{x \to 0} \frac{(1-\frac13x + O(x^2)-1)}{4^x ( -x \ln(3/4)+O(x^2))}= \lim_{x \to 0} \frac{-\frac13 x}{ -x\ln3/4 }=-\frac1{3\ln4/3}.$